2016
DOI: 10.1097/mpg.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Pediatric Gastroenterology

Abstract: Preferences and practices surrounding transition preparation and transfer to adult care vary widely, reflecting continued uncertainty regarding optimal transition strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Pediatric subspecialists in other fields report caring for patients into their mid-20s or 30s in pediatric clinics. 24,25 Providers who practice at free-standing children's hospitals and have been in practice longer have been shown to be more likely to care for patients into adulthood. 26 Age is not the only factor that acts as a catalyst for the transfer to adult care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric subspecialists in other fields report caring for patients into their mid-20s or 30s in pediatric clinics. 24,25 Providers who practice at free-standing children's hospitals and have been in practice longer have been shown to be more likely to care for patients into adulthood. 26 Age is not the only factor that acts as a catalyst for the transfer to adult care.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived readiness for an adult model of care, as well as life milestones such as graduation or marriage, may all prompt transfer. 24,25,27,28 Pediatric subspecialists across many fields report transferring patients when they become pregnant, develop adult comorbidities, or are found to abuse illicit substances or alcohol, which sometimes lead to precipitous transfer of patients who have not yet achieved readiness. 29 In contrast, clinicians may be hesitant to transfer patients with ongoing active disease, upcoming planned procedures, or endstage disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this direction, Bensen et al showed in a national paediatric gastroenterology survey that there is tremendous variability in practice across all diseases but especially IBD (48% of respondents) ( 11 ). Gray et al also recently showed that only 50% of American paediatric gastroenterologist survey respondents were familiar with current recommendations and less than 1% based their practices entirely on them ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of patients with IBD, the transfer typically requires a request for consultation from the pediatric gastroenterologist to the adult provider, accompanied by a summary letter describing the details of the patient’s disease, treatments, complications and psychosocial history ( 6 , 7 ). In a survey of adult gastroenterologists, the sub-optimal quality of the documentation sent by pediatricians was identified as one of the barriers to a successful transfer to adult care ( 8 , 9 ). A template for a transfer letter was included in the transition guidelines produced by The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) ( 10 ).…”
Section: Introductionmentioning
confidence: 99%